Gold(I) complexes based on six-membered phosphorus heterocycles as bio-active molecules against brain cancer - Rösch, Saskia; Fermi, Valentina; Rominger, Frank; Herold-Mende, Christel; Romero-Nieto, Carlos (Chemical communications, 2020)
π-Systems based on six-membered phosphorus heterocycles possess structural and electronic characteristics that clearly distinguish them from the rest of the organophosphorus molecules. However, their use in cancer therapy has been uninvestigated. In particular, glioblastoma is one of the most lethal brain tumors. The development of novel and more efficient drugs for the treatment of glioblastoma is thus crucial to battle this aggressive disease. Herein, we report a new family of gold(I) complexes based on six-membered phosphorus heterocycles as a promising tool to investigate brain cancer. We discovered that the latter complexes inhibit the proliferation, sensitize to apoptosis and hamper the migration of not only conventional but also stem-like glioblastoma cells. Our results unveil thus new research opportunities for the treatment of glioblastoma.
Gesehen am 28.01.2021